Going low to reach high: Small‐scale ChIP‐seq maps new terrain. (3rd September 2019) - Fosslie, Madeleine; Manaf, Adeel; Lerdrup, Mads; Hansen, Klaus; Gilfillan, Gregor D.; Dahl, John Arne
Abstract: Chromatin immunoprecipitation (ChIP) enables mapping of specific histone modifications or chromatin‐associated factors in the genome and represents a powerful tool in the study of chromatin and genome regulation. Importantly, recent technological advances that couple ChIP with whole‐genome high‐throughput sequencing (ChIP‐seq) now allow the mapping of chromatin factors throughout the genome. However, the requirement for large amounts of ChIP‐seq input material has long made it challenging to assess chromatin profiles of cell types only available in limited numbers. For many cell types, it is not feasible to reach high numbers when collecting them as homogeneous cell populations in vivo. Nonetheless, it is an advantage to work with pure cell populations to reach robust biological conclusions. Here, we review (a) how ChIP protocols have been scaled down for use with as little as a few hundred cells; (b) which considerations to be aware of when preparing small‐scale ChIP‐seq and analyzing data; and (c) the potential of small‐scale ChIP‐seq datasets for elucidating chromatin dynamics in various biological systems, including some examples such as oocyte maturation and preimplantation embryo development. This article is categorized under: Laboratory Methods and Technologies > Genetic/Genomic Methods Developmental Biology > Developmental Processes in Health and Disease Biological Mechanisms > Cell Fates Abstract : Standard native (N)ChIP and cross‐linking (X)ChIP protocols are not suitable for low cell number samples. This article reviews advances central to downscaling of the ChIP method, important examples of biological insights revealed by small‐scale ChIP‐seq experiments, and delineates important considerations when performing ChIP‐seq with limited amounts of material.